A comparison of the cumulative incidence and early risk factors for psychotic disorder in young adults in the Northern Finland Birth Cohorts 1966 and 1986. (28th March 2016) - Filatova, S.; Marttila, R.; Koivumaa-Honkanen, H.; Nordström, T.; Veijola, J.; Mäki, P.; Khandaker, G. M.; Isohanni, M.; Jääskeläinen, E.; Moilanen, K.; Miettunen, J.
Abstract : Aims: Few studies have compared time trends for the incidence of psychosis. To date, the results have been inconsistent, showing a decline, an increase or no significant change. As far as we know, no studies explored changes in prevalence of early risk factors. The aim of this study was to investigate differences in early risk factors and cumulative incidences of psychosis by type of psychosis in two comparable birth cohorts. Methods: The Northern Finland Birth cohorts (NFBCs) 1966 ( N = 12 058) and 1986 ( N = 9432) are prospective general population-based cohorts with the children followed since mother's mid-pregnancy. The data for psychoses, i.e. schizophrenia (narrow, spectrum), bipolar disorder with psychotic features, major depressive episode with psychotic features, brief psychosis and other psychoses (ICD 8–10) were collected from nationwide registers including both inpatients and outpatients. The data on early risk factors including sex and place of birth of the offspring, parental age and psychosis, maternal education at birth were prospectively collected from the population registers. The follow-up reached until the age of 27 years. Results: An increase in the cumulative incidence of all psychoses was seen (1.01% in NFBC 1966 v . 1.90% in NFBC 1986; p < 0.001), which was due to an increase in diagnosed affective and other psychoses. Earlier onset of cases and relatively more psychoses in women were observed in the NFBC 1986. Changes in prevalence of potential early risk factors were identified, but only parental psychosis was a significant predictor in both cohorts (hazard ratios ≥3.0; 95% CI 1.86–4.88). The difference in psychosis incidence was not dependent on changes in prevalence of studied early risk factors. Conclusions: Surprisingly, increase in the cumulative incidence of psychosis and also changes in the types of psychoses were found between two birth cohorts 20 years apart. The observed differences could be due to real changes in incidence or they can be attributable to changes in diagnostic practices, or to early psychosis detection and treatment.